Power, Gender, and Loss of Identity in Brit Bennett's The Mothers (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article probes into the themes of power, gender, and loss of identity in Brit Bennett's celebrated novel, The Mothers, through the theoretical lens of Homi K. Bhabha's concepts of hybridity, mimicry, third space, and ambivalence. Drawing upon Bhabha's postcolonial framework, this analysis examines how these concepts intersect and contribute to the narrative of the novel, ultimately portraying the complexities of personal and social identity formation. Through an exploration of hybridity, the article investigates how the characters in The Mothers negotiate multiple cultural and social influences within a contemporary American context. It examines the ways in which the protagonists navigate the tensions and conflicts that arise from their overlapping identities, challenging normative expectations and highlighting the intricate intersections of race, class, and gender.Furthermore, the article analyzes the theme of mimicry, whereby characters adapt and imitate cultural and social practices to negotiate their position within society. It investigates how mimicry acts as a tool for survival, while also exploring its potential to reinforce power dynamics and perpetuate inequalities. Building on Bhabha's concept of the third space, the article inspects the liminal spaces within the novel where characters negotiate their identities, neither fully assimilating nor completely retaining their original cultural or social markers. Through this examination, the article represents the transformative possibilities of these spaces and their potential to challenge traditional power structures.Lastly, the article investigates the theme of ambivalence, which reflects the simultaneous presence of conflicting emotions, ideologies, and identities within the characters of The Mothers. It delves into how ambivalence operates as a site of tension, resistance, and agency within the narrative, ultimately shaping the characters' quests for self-discovery and empowerment. In sum, by employing Bhabha's theoretical framework, this article offers a nuanced exploration of power, gender, and loss of identity in The Mothers. , and illuminates the complexities of identity formation, exposing the multifaceted ways in which individuals navigate and resist societal norms and power dynamics.